Pengaruh Faktor Predispocing, Reinforcing dan Enabling terhadap Perilaku Seksual Pranikah pada Mahasiswa Akper Berkala Widya Husada Jakarta - Mustikawati Mustikawati; Muhammad Anhar (STIKes Persada Husada Indonesia, 2014)
Lack of knowledge about adolescent reproduction health, bad behaviours, positive attitude towards sexual acts are issupporting factors of the free sex behaviour. The role of parents, and the PA in providing information about ARH are essential to avoid premarital sexual behavior, the role of peers, and the exposure of pornographic media may also affect the behavior. With the contraception are easily available and often dating can also increases the attitude towards premarital sexual behavior. This is supported by health behavior theory by L. Green consisting of three factors: predisposing factors, contributing factors (enabling) and the drivers (reinforcing), individuals can change their behavior for the better. This study aimed to determine the influence predispocing, reinforcing and enabling of premarital sexual behavior of Berkala Widya Husada Nursing Student DIII Jakarta in 2011, with quantitative research methods that use cross-sectional design with a sample of 156 students. The results of this study influenced the enabling premarital sexual behavior for DIII Nursing student at Berkala Widya Husada with the T-statistics of 13, 583 485 or eligible T> 1.96 at CI = 95%. The magnitude of the parameter coefficient of 0.578657 means that there positive enabling influence on premarital sexual behavior. The lack of influence of predisposing and reinforcing in premarital sexual behavior with the results of less than 1.96 at 95% CI.